Perkembangan Institusi Keuangan Non-Bank Islam di Indonesia (Studi Kasus Pegadaian Syariah) - Arifa, Marisa Nur (Educationist: Journal of Educational and Cultural Studies, 2023)
This research aims to determine the integration of understanding between the theories that have been studied and the practices that occur in the world of work, as well as human resources to deal with the development of non-bank Sharia financial institutions in Indonesia. Sharia banking financial institutions, working in sharia finance non-bank institutions such as pawnshops, sharia insurance, ammil zakat institutions, and Baitul Maal wa Tamwil prioritize the value of society. Relationships with customers are not only customers with institutions, but also family relationships among people. This paper uses the method of analysis of literature reviews and to examine research related to the history and development of Pawnshops in Indonesia. The results showed that Pawnshops in Indonesia are close to Islamic idealism. This can be seen in terms of the fact that the financing system, storage costs, auction deadlines, and there is often a misunderstanding between the pawnshop and the community, due to the lack of adequate facilities of pawnshops as well. Thus, massive education is very important to improve people's knowledge.